Association between kidney function and hearing impairment among middle-aged and elderly individuals: a cross-sectional population-based study. Issue 6 (18th August 2021) - Yang, Dong; Guo, Huiying; Guo, Dandan; Wang, Zhenyu; Guo, Sitong; Liu, Jie; Wang, Mingxin; Xu, Yi; Zhang, Peng; Wang, Gaoyu; Zhang, Jing; Ning, Xianjia; et al.
ABSTRACT: Objective: As age-related diseases, chronic kidney disease and hearing impairment (HI) cause a serious socioeconomic burden. Due to structural similarities, there is a certain connection between kidney function and hearing, but there has been no large-scale epidemiological study in China that further explored this connection. Thus, this study aimed to explore the association between indicator levels of kidney function and hearing impairment among middle-aged and elderly individuals in Tianjin, China. Method: In 2020, 1539 participants aged 45 years or older from Tianjin, China, were recruited into this study. All participants completed questionnaire surveys and underwent physical examinations, laboratory examinations, and hearing tests. The estimated glomerular filtration rate (eGFR) was calculated from serum creatinine (Cre) levels. HI was measured using pure-tone audiometry, and audiologists determined the final diagnoses. Result: The prevalence of HI was 49.97%. With each 1-mL/min/1.73 m 2 increase in eGFR, the overall odds of HI increased by 1.3%; the risk increased by 2.4% and 1.6% for men and people aged 45–65 years, respectively. In contrast, in women, the odds of HI increased as Cre levels increased. Moreover, with each 1-mL/min/1.73 m 2 increase in eGFR, the overall odds of a one-degree increase in hearing loss increased by 1.7%; the odds increased by 2.3% and 1.5% for men and people aged 45–65 years, respectively. However, in women and people aged ≥65 years, the odds of a one-grade increase in hearing loss increased by 2.1% and 1.5%, respectively, with each 1-µmol/L increase in Cre. In addition, there were no significant relationships between blood urea nitrogen and hearing loss in multivariate analysis (all P > 0.05). Conclusions: These findings suggest that eGFR and serum Cre are effective predictors of hearing loss. Thus, to decrease the burden of HI, hearing should be carefully monitored for people aged ≥45 years with elevated serum Cre and eGFR.